MAKNA SOSIALITA DALAM FILM ARISAN 2 - Sofi Adenina (MediaKom : Jurnal Ilmiah Komunikasi, 2017)
The socialite is a super rich person who doesn't need to work and yet no one can doubt their wealth. They use their fortune to   conduct social activities aimed at the public interest. By viewing the function of the mass media who have a noble duty to provide information, education, and also medium values of social inheritance, the film Arisan 2 became a social paradox. In the movie Arisan 2, there are a lot of signs, both in the form of audio or visual conflict with the noble task. Through a semiotic analysis of Roland Barthes who use relationships meaning as a mark through the stages of significance denotation, connotation and myth, it turns out that the mythology which exists in the community about the socialite not only strengthened. Yet in the Arisan 2 movie, there has been a shift in mythology where the socialite now is a group of people who need the acknowledgement that they are rich, and it is the goal of live for every human being. Mass media has lost its noble task. As a medium it has now become an active transmitter in the formulation of reality, not to mention the reality of the socialite.Keywords: Meaning, Socialite, Film, Semiotics